Aula de Trabalho Pedagógico Coletivo: atividade crítica de colaboração? - Cacero, Eliana Maciel (2016)
This research aims at understanding the socio-historical-cultural context of Collective Pedagogical Work Class (Aula de Trabalho Pedagógico Coletivo - ATPC) and develops a proposal for the education of ATPC as a critical collaborative space. During the process, we intended to describe ATPC socio-historical-cultural context in São Paulo Secretary of Education and in two State Schools, located in the eastern region of São Paulo. Based on the descriptions, we planned an education proposal for educators, which subsidize Teacher Coordinators to develop ATPC as a collaborative critical space. The chosen methodology was the Critical Collaborative Research (MAGALHÃES, 2011), which allows intervention in school practices through the understanding of socio-historical-cultural context, the collaborative relations among the research subjects and the redefinition of school practices. The survey was conducted with two Teacher Coordinators from the final years of elementary school, the sector in which the researcher is an educator. The focal pedagogical practice is critical collaboration at ATPC. The instruments used to for the analyses were the audio of the ATPCs meetings and the questionnaire answered by the Teacher Coordinators. The theoretical framework was guided by discussions on collaboration and critical thinking in the light of Social-Historical-Cultural Activity Theory (TASHC) and on critical education. Analyses were conducted based on the components of Social-Historical-Cultural Activity Theory, which allowed us to visualize ATPC as an activity and identify if and how critical collaboration happens in this context. The understanding of the results allowed us to develop an education proposal for ATPCs as a critical collaborative space